2021
DOI: 10.1002/suco.202000737
|View full text |Cite
|
Sign up to set email alerts
|

Bond behavior of plain round bar embedded in high ductile concrete under monotonic and cyclic loading

Abstract: Bond behavior is the basis of combined action of steel bar and high ductile concrete (HDC), which has an important effect on the mechanical performance of reinforced HDC structures. In this paper, nine groups of pullout specimens were tested to investigate the bond behavior and degradation mechanism of plain round bar embedded in HDC under monotonic and cyclic loading. The design parameters included HDC compressive strength, HDC flexural toughness and anchorage length. Experimental results indicated that only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Thus, to make the studies on the bond performance close to the actual seismic condition, some researchers conducted the bonding tests under cyclic loading. Pan et al [ 27 ] reported the bond behavior of plain bars in highly ductile concrete under repeated loading, in which the loads was applied positively and unloaded to zero in each loading cycle and the bond behavior of PE fiber and PVA fiber-reinforced specimens was analyzed. Verderame et al [ 28 , 29 ] conducted experimental and analytical investigations on the bond behavior of plain bar in low-strength concrete under cyclic loading, where plain bars with a diameter of 12 mm and a yield strength of 330 MPa and the concrete with a compression strength of 15.9 MPa were adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to make the studies on the bond performance close to the actual seismic condition, some researchers conducted the bonding tests under cyclic loading. Pan et al [ 27 ] reported the bond behavior of plain bars in highly ductile concrete under repeated loading, in which the loads was applied positively and unloaded to zero in each loading cycle and the bond behavior of PE fiber and PVA fiber-reinforced specimens was analyzed. Verderame et al [ 28 , 29 ] conducted experimental and analytical investigations on the bond behavior of plain bar in low-strength concrete under cyclic loading, where plain bars with a diameter of 12 mm and a yield strength of 330 MPa and the concrete with a compression strength of 15.9 MPa were adopted.…”
Section: Introductionmentioning
confidence: 99%
“…As a key factor to evaluate the bond performance, the bond strength has been tested by a large number of pullout specimens 13 or beam specimens. 14,15 Various parameters that affected the bond strength were taken into account, such as bar diameter, 16 cover thickness, 17 bond length, 18 and so on. Then the predicted model of bond strength was built by the regression analysis of experimental data.…”
Section: Introductionmentioning
confidence: 99%